Love for sale : courting, treating, and prostitution in New York City, 1900-1945 - Clement, Elizabeth Alice (Gender & American culture., 2006)
Comparing prostitution and courtship with a new working-class practice of heterosexual barter called 'treating' during the period between 1900 and 1945, this book examines changes in sexual morality and sexual and economic practices in New York.